Barriers and facilitators to recruiting and retaining men on pre-registration nursing programmes in Western countries: A systemised rapid review. (May 2020) - Gavine, Anna; Carson, Maggie; Eccles, Jacqueline; Whitford, Heather M.
Abstract: Background: The recruitment of men to pre-registration nursing programmes in many Western countries has remained static at approximately 10% per year. Aim: To identify the experiences and attitudes of men on pre-registration nursing programmes in Western countries and the barriers and enablers to their recruitment and retention. Design: Systematized rapid review. Methods: Searches were undertaken in Medline (Ovid), CINAHL (EBSCO) and PsychINFO (EBSCO) databases. Studies in English were included if they were from Western countries, were published since 2000 and related to men's experiences of, or attitudes to, applying for or studying pre-registration nursing. Included papers were quality appraised and findings were thematically analysed and presented in a narrative synthesis. Results: Records were de-duplicated and 2063 records were screened and 44 articles assessed for eligibility of which 23 articles relating to 22 empirical studies were included in the review. Findings were categorised into the following themes: recruitment experiences/reasons for studying nursing; gender experiences; barriers, difficulties and challenges with programme; and factors affecting retention. Conclusion: Evidence suggests that many men who come into nursing have a family member or acquaintance who is a nurse or that they have had contact with a male nurse as a patient or carer. Motivating factors such as financial security, career mobility and the opportunity to have a job in a caring profession were reported. Improved career advice at school is needed and shortened graduate programmes could be attractive. On programme, some clinical areas were easier for male students, while in others, treatment refusal could cause difficulties. Being in a minority and gender stereotyping can affect experiences. Ensuring equitable treatment, providing additional support and placements in clinical areas with more men could minimise these challenges.